Qualitative research methods in medical dissertations: an observational methodological study on prevalence and reporting quality of dissertation abstracts in a German university - Ullrich, Charlotte; Stürmlinger, Anna; Wensing, Michel; Krug, Katja (BMC medical research methodology, 2020)
Qualitative methods offer a unique contribution to health research. Academic dissertations in the medical field provide an opportunity to explore research practice. Our aim was to assess the use of qualitative methods in dissertations in the medical field.